Nilotinib treatment induced large granular lymphocyte expansion and maintenance of longitudinal remission in a Philadelphia chromosome-positive acute lymphoblastic leukemia - Hagihara, Masao; Hua, Jian; Inoue, Morihiro; Uchida, Tomoyuki; Ide, Shiro; Ohara, Shin; Takaku, Tomoiku (International Journal of Hematology, 2020)
It is well known that the second-generation tyrosine kinase inhibitor dasatinib evokes an immunological reaction as an off-target effect and induces large granular lymphocytes (LGLs) expansion in 30% of patients. However, LGLs expansion in nilotinib-treated patients is rare. We report the case of a 65-year-old patient with Philadelphia chromosome (Ph)-positive acute lymphoblastic leukemia (ALL) who showed LGLs expansion during nilotinib treatment. The patient achieved complete remission (CR) after multi-agent chemotherapy combined with dasatinib treatment. However, ALL relapsed in the central nervous system and bone marrow when treatment was interrupted due to interstitial pneumonia. Nilotinib treatment was subsequently started and the patient achieved second CR. Marked peripheral blood lymphocytosis emerged after the start of nilotinib treatment. CD8 + CD57 + cytotoxic T cells were predominantly expanded and showed strong cytocidal activity against K562 Ph-positive leukemia cells. These results suggest that similar to dasatinib, nilotinib can induce LGLs expansion, possibly contributing to long-term remission in patients with Ph-ALL.